Child/adolescent caring for the disabled sibling in the family world - Vera Lucia Freitag; Maria da Graça Corso da Motta; Viviane Marten Milbrath; Ruth Irmgard Bärtschi Gabatz; Jéssica Stragliotto Bazzan (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To understand the meaning for the child/adolescent of participating in the care of the disabled sibling. Method: Research in the light of the Heideggerian phenomenological approach, carried out in the northern region of Rio Grande do Sul - Brazil. Twenty children/adolescents who lived with their disabled sibling participated. The information was collected through phenomenological interviews, interpreted in the light of hermeneutics from Paul Ricoeur. Results: The child/adolescent helps the family in caring for the disabled sibling, in feeding, bathing, dressing, among other activities, at sometimes there is excessive responsibility of the child/adolescent for the care of the sibling. Final considerations: The inclusion of the child/adolescent who lives with a disabled sibling and their families in the planning and implementation of health care activities is essential. It stands out as a research contribution to the qualification of the practice of health professionals, especially the nurse in the scope of care for the child/adolescent who experience this phenomenon.